Disseminated Herpes Zoster in an Immunocompromised Geriatric Patient: Disseminated Herpes Zoster in Geriatric Patient - Muhtady, N.F.A; Nurasrifah , D.I; Indraswari , A; Reza, N.R; Alinda, M.D; Widia, Y; Agusni , R; Hidayati, A. N (Future Science, 2021)
Disseminated Herpes Zoster (DHZ) was defined as the presence of 25–50 or more blisters outside the primary or near the dermatomal area that usually occurred within a week of the onset of the primary lesion. It is rare and occurs much less frequently than generalized herpes zoster infection, with most cases developing in immunocompromised patients. Case: A 60-year-old woman complained of grouped multiple blisters with an erythematous base three days before. She came to ER and noticed a stabbing pain and burning sensation on the external ear and left neck. The patient also complained of fever one day before the lesion occurred. The blisters were already ruptured the next day, and some erosion was seen and covered by black crust. On day 5, she also complained of blisters spreading on her back and felt itchy but no pain. She has been suffering from a mild cough for more than a year. Chest X-ray found ground glass opacity paracardial right and left, indicating pneumonia. She has had a history of hearing impairment since 15 years ago. She is unmarried and lives alone. The result of the Tzanck smear examination indicated several multinucleated giant cells. Acyclovir 800 mg 5 times daily was administered to the patient for ten days. Ceftriaxone 1g twice a day and Antrain 1 g 3 times daily. Debridement therapy with normal saline 0,9% were also included. Conclusion: A DHZ case can affect immunocompromised geriatric patients.